Experimental Study on Strengthening Near-Surface of Slopes Using Bio-grouting Technique - Gowthaman, S.; Nakashima, K.; Nakamura, H.; Kawasaki, S. (Springer, Singapore, 2021)
Near-surface instability due to incessant rainfall events poses challenges to the maintenance of earth structures. Bio-grouting (also be referred to as microbial induced carbonate precipitation (MICP)) is a recently emerged soil improvement technique, revealing high potential for stabilizing near-surface of slopes. The technique promotes the cementation of embedded soil using calcium carbonate that precipitates biochemically. This paper presents a bench-scale experimental program, and the objectives were (i) to understand how the treatment protocols impact the strengthening of near-surface and (ii) to assess the profile of treated slope. For those, a series of slope models was treated by various experimental protocols using surface spraying technique. During the treatment, bacteria culture and cementation resources were sprayed in two subsequent phases. The findings suggest that the bio-grouting responses vary depending on volume of cementation solution supplied. High supply of cementation solution developed a highly nonuniform-treated profile compared with low supplies. Also, 1 mol/L concentration of cementation solution is found to be the optimum for the treatment, providing strong intergranular bridging. The spatial distribution of calcium carbonate showed the treated slope can be considered into three layers: surface-crust layer, cemented soil layer and uncemented soil, suggesting that the application technique may provide erosion protection via the crust formed along the outer surface of the slope and cemented soil material formed on the interior.
Keywords: Microbial induced carbonate precipitation (MICP).; Slope near-surface.; Surface spraying.; Slope model.; Calcium carbonate.